Advancements in multi-scale filler reinforced epoxy nanocomposites for improved impact strength: A review. Issue 4 (4th July 2021) - Nanda, Tarun; Singh, Karanbir; Shelly, Daksh; Mehta, Rajeev
Abstract: Epoxy-clay fiber reinforced plastics are employed in myriad applications. They, however, are brittle with less impact strength/related properties. There has been tremendous amount of research on processing of epoxy based glass fiber reinforced plastics (GFRPs) nanocomposites for obtaining good mechanical properties, especially impact strength. This review initially explains various clay morphologies in polymer-nanocomposites, and makes a care for compatibilization of reinforcing fillers. It discusses contribution of researchers with regard to: epoxy-layered silicate nanocomposites, epoxy-clay based GFRPs, polymer/elastomer modified composites, surface modification procedures for polymer/elastomer fillers, and multi-scale filler reinforced GFRPs. The key to improved impact strength of multi-scale filler reinforced epoxy GFRPs lies in good compatibility of polymeric/elastomeric fillers with other constituents. Various techniques for this purpose have been discussed. Most recent developments where researchers have processed epoxy GFRPs containing clay as nano-filler and compatibilized thermoplastic-fibers/elastomeric-particles as micro-filler providing improved impact strength/tensile properties have been described. Finally, scope of future research has been presented.